Understanding human genetic variation in the era of high-throughput sequencing. - Knight, J (2010)
The EMBO/EMBL symposium 'Human Variation: Cause and Consequence' highlighted advances in understanding the molecular basis of human genetic variation and its myriad implications for biology, human origins and disease. As high-throughput sequencing allows us to define genetic variation and its functional consequences at genome-wide resolution for a large number of people, important questions need to be asked about how to use new technologies to maximize the translational relevance of genetic research for society and the individual patient.